Asian perspectives on human right/ edited by Claude E. Welch and Virginia A. Leary - "Leary, Virginia A. (ed.) ; Welch, Claude E. (ed.)" (Boulder, 1990)
This book deals with human rights in Asia
Keywords: Civil rights